Evaluasi Media Pembelajaran Interaktif Pengenalan Tata Surya dengan Teknologi Augmented Reality dan Virtual Reality - Fendi Aji Purnomo; Sastri Jendra Ayuningrat; Yoana Lukitasari; Arrofvianti Nurwhinda Kusuma (Teknodika, 2020)
The solar system is something that is learned but cannot be seen directly by students. Planet props available in laboratory are also very limited and presented in conventional models so that students are less interested in learning further with the existing planetary models. This study aims to evaluate the results of making astronomy learning media applications with Augmented Reality and Virtual Reality technology. This application is designed and developed using the MDLC method, namely concept, design, material collecting, assembly, testing and distribution stages. This interactive media is packaged using Augmented Reality and Virtual Reality technology which are presented in interactive catalog. This study have created the Android-based learning media of the Milky Way Galaxy Planet System. The material is presented in form of discussion about the Solar System that is taught in Middle School. This application can be run optimally with Quadcore 1.5 Ghz device specifications which has 3 GB RAM and gyro sensor. The assessment results from junior high school students on Design and Information Aspects get a Very Good and Very Good grades of 100%, then Navigation Aspects scores of 99.9%.